(untitled) (Journal of Universal Science Research, 2023)
The article discusses the features of research in the field of logic. The work gives characteristics of logical and non-logical terms, examines the features of empirical and theoretical logical terms, and provides logical and methodological criteria for the scientific and non-scientific nature of knowledge.